ANALISIS FAKTOR PERSEPSI KERENTANAN IBU TERHADAP PEMANFAATAN KELAS IBU HAMIL DI PUSKESMAS GAYAMSARI KOTA SEMARANG - Celica Triulfah Maharani; Ayun Sriatmi; Antono Suryoputro (Jurnal Kesehatan Masyarakat (Undip), 2018)
Semarang city ranks in top 3 of maternal mortality case rate in Central Java province, with the highest occurance during 2017 has been found in Gayamsari health center. It is known that the government has a program called Kelas Ibu Hamil (KIH) or pregnancy class as an effort to reduce mortality rate, but it still lacks attendance of said mothers. This study aims to analyze the mothers perceived susceptibility towards utilization of pregnancy class. This study is a qualitative study using a depth interview method to 12 informants. The result shows that 4 respondents have risk factors for pregnancy. But not all the respondents will attending the pregnancy class. Another factors were found that there was a connection with mother’s lack of understanding about pregnancy class toward their attending in pregnancy class. And few mothers still constrained to attend due to their schedule work. It is expected that health centers should make anticipation such as giving initial information about pregnancy class to mother and need to adjust the schedule of pregnancy class to mother, thus increasing pregnancy class attendance.